Nitrogen management of corn with sensor technology - Tucker, Andrew Neil (Kansas State University, 2010)
Corn (Zea mays) is an important cereal crop in Kansas primarily used as livestock feed for cattle in the feedlots, and there has been increased use of corn for ethanol production as well. According to the USDA National Agriculture Statistics approximately 1.7 million hectares of corn is planted each year in Kansas, with an average yield ranging from 5,750-7,750 kg ha[superscript]-1 within the last five years (2005-2009). With this variability in yield and volatility of crop and fertilizer prices over that same period, it seems logical that optimum nitrogen or N rates may vary. A series of 14 field experiments were conducted across Kansas from 2006 through 2009 to address this issue. Specific experiments included: evaluating optimum N rates from side-dressing nitrogen fertilizer; timing of nitrogen application, pre-plant vs. split applications and normal side-dress V-6-V-9 vs. late side-dress V-14-V-16; N response of corn to a late side-dress of nitrogen fertilizer; and the evaluation of optical sensors for making in season N recommendations. The specific objectives of this research were to: a. Determine the optimum N application rate and timing to optimize corn grain yields in different corn producing regions in Kansas. b. Confirm or revise the current K-State soil test based N recommendation system for corn. c. Evaluate N management strategies using the GreenSeeker, Crop Circle, and SPAD meter, crop sensors. d. Develop draft GreenSeeker, Crop Circle, and SPAD sensor algorithms for producers to use. Grain corn yields were responsive to N at all but 3 sites. Grain yields obtained at the sites ranged from 3,460 to 15,480 kg ha[superscript]-1. Optimum N rates varied from 0 to 246 kg N ha[superscript]-1. This work suggests that current K-State N fertilizer recommendations for corn need revisions due to over recommendation of N. Including different coefficients for irrigated and dry land corn along with N recovery terms would create a more accurate N recommendation system that more closely reflects the results obtained in these experiments, and provide a significant improvement over the current system. The optical sensors used in this study were effective at making N recommendations for corn. These sensors can be a valuable tool for producers to use and determine in season N status of corn.
Keywords: Sensor Corn Nitrogen; Agriculture, Agronomy (0285)